The E-box Binding Factors Max/Mnt, MITF, and USF1 Act Coordinately with FoxO to Regulate Expression of Proapoptotic and Cell Cycle Control Genes by Phosphatidylinositol 3-Kinase/Akt/Glycogen Synthase Kinase 3 Signaling - Terragni, Jolyon (American Society for Biochemistry and Molecular Biology, 2011)
Phosphatidylinositol (PI) 3-kinase/Akt signaling plays a critical role in cell proliferation and survival, partly by regulation of FoxO transcription factors. Previous work using global expression profiling indicated that inhibition of PI 3-kinase in proliferating cells led to induction of genes that promote cell cycle arrest and apoptosis. The upstream regulatory regions of these genes had binding sites not only for FoxO, but also for Myc/Max transcription factors. In the present study, we have addressed the role of Myc family members and related E-box-binding proteins in the regulation of these genes. Chromatin immunoprecipitations and RNA interference indicated that transcription was repressed by Max-Mnt-Sin3a-histone deacetylase complexes in proliferating cells. Inhibition of PI 3-kinase led to a loss of Max/Mnt binding and transcriptional induction by MITF and USF1, as well as FoxO. Both MITF and USF1 were activated by glycogen synthase kinase (GSK) 3, with GSK3 phosphorylation sites on USF1 identified as the previously described activating site threonine 153 as well as serine 186. siRNA against MITF as well as against FoxO3a protected cells from apoptosis following PI 3-kinase inhibition. These results define a novel E-box-regulated network that functions coordinately with FoxO to regulate transcription of apoptotic and cell cycle regulatory genes downstream of PI 3-kinase/Akt/GSK3 signaling.